Interaction between Food and Anticoagulants in Patients with Cardiovascular Diseases - Rudina Prifti; Manika Kreka (European Scientific Journal, ESJ, 2022)
Cardiovascular diseases are one of the most common diseases in the world. Anticoagulants and other drugs are prescribed as a treatment for these diseases. However, polypharmacy may increase the risk of drug-drug or food-drug interactions and decrease patient compliance. Food-drug interactions may put the patient at risk for serious adverse effects and reduce the safety and efficacy of treatment. Food‐drug interaction is a common problem that has occurred as a result of the concomitant use of multiple drugs with food. Food-drug interaction is the term used to describe how food affects a medication in the body. Food can alter the effectiveness of the medication, make unwanted side effects better or worse, or even bring on brand-new negative effects. Drugs may alter how the body processes food. Consumption of foods that contain vitamin K makes anticoagulant therapy less effective. On the other hand, patients should be careful when consuming foods like garlic, ginseng, ginger, and ginkgo to avoid the undesirable effect of hemorrhage. Among the medical records examined, no advice or recommendations were provided regarding anticoagulant-food interactions, no details about the time of taking anticoagulant drugs and the exact time of eating meals were given and there were few instances in which medicine dosage was altered due to a food association.  A majority of patients who completed an anonymous survey in community pharmacies were not informed about food-drug interactions. Healthcare professionals should advise patients taking anticoagulants to be careful with the food they consume and clinicians should manage the time and dose variability of the medicine so a successful therapy can be achieved.